THE RELATIONSHIP BETWEEN PROFESSIONAL SPECIALIZATION AND EDUCATIONAL ACHIEVEMENT AMONG NURSING, SURGERY, AND ANESTHESIA STUDENTS IN SAUDI ARABIA - Ahlam Bandar Alshammari, Abdullah Mohammed Moslem Aljohani, Samar Abdullah Saleh Al Saleh, Sultan Awad Aljohani, Tamany Saif Alruwaili, Ahmad Abdulmuti Aljhni, Omar Awwadh Nashi Almaghthawi, Sultan Salem Rashed Alharbi, Hamdan Hudayban Alouf; Marwan Khulaif Alahmadi,Turky Aedh Alharbi (Chelonian Research Foundation, 2022)
This study investigates the relationship between professional specialization and educational achievement among nursing, surgery, and anesthesia students in Saudi Arabia. A cross-sectional survey design was employed, and data were collected from a sample of 437 students enrolled in nursing, surgery, and anesthesia programs at various universities in Saudi Arabia. The study aimed to determine if there were significant differences in educational achievement across the three specializations and to identify the factors contributing to these differences. One-way ANOVA and multiple linear regression analyses were conducted to examine the differences in educational achievement and determine the predictive effects of professional specialization on educational achievement, while controlling for demographic variables. The findings revealed significant differences in educational achievement across the three specializations, with nursing students outperforming their peers in surgery and anesthesia. The regression analysis confirmed the significant predictive effect of professional specialization on educational achievement, even after controlling for demographic variables. The study highlights the importance of considering the unique characteristics and demands of each specialization when developing strategies to enhance educational achievement among healthcare students in Saudi Arabia. Universities should tailor their support and interventions to address the specific needs and challenges faced by students in different healthcare specializations.